Community Partnership Program of Making Liquid Organic Fertilizer from Fish Waste in Pedungan Village, Denpasar - Ni Made Darmadi; I Gusti Made Arjana; Dewa Gede Semara Edi; Hitler Sumah; I Kadek Riko Adi Antara (PT FORMOSA CENDEKIA GLOBAL, 2023)
The concept of implementing Blue Economy is highly expected in this activity. The implementation of Zero Waste of Community Partnership Program conducted at Ni Wayan Sarimi’s household industry turned waste into Liquid Organic Fertilizer. The purpose is to provide Liquid Organic Fertilizer Manufacturing Technology in managing tuna skin waste. The method began with partner’s application to Service Team, doing examination and interview by the team to find out the partner’s problems. The team conducted Counseling related to Liquid Organic Fertilizer Production, Packaging, and Marketing and did practicing three (3) times. The results include making Liquid Organic Fertilizer properly, having new products with good packaging to be sold, publishing activities on Electronic Media or Journals, and uploading activities videos on YouTube.